Challenges and opportunities toward enabling phenotypic screening of complex and 3D cell models. (March 2015) - Horman, Shane R; Hogan, Christopher; Reyes, Karlo Delos; Lo, Frederick; Antczak, Christophe
Increasingly, organotypic cellular platforms are being recognized as useful tools in drug discovery. This review offers an industry-centric perspective on the benefits of emerging complex cell models over conventional 2D systems, as well as the challenges and opportunities for incorporating these multidimensional platforms into high-density formats. We particularly highlight the need for novel chemical sensors to noninvasively quantitate 3D structures in real time, and we contend that the use of more focused chemical and genomics libraries will enable screening of complex cell models derived from primary and induced pluripotent stem cells. Finally, we offer outlooks on several emerging technologies that show great potential for future integration of complex cell systems into contemporary drug screening.